(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article studies the effects of temperature, biostimulants, and planting conditions on the germination of seeds of the tropical plant Crotalaria juncea in field conditions. The studies were conducted in the climatic conditions of the Jizzakh region, and it was found that the seeds reached 99–100% germination at a temperature of 29–33℃. In field experiments, the use of biostimulants increased seed germination by 4.6–7.4% compared to the control option. In particular, the Geohumat stimulator was more effective than UzGumi. The results of this study confirm that Crotalaria is resistant to high temperatures, germinates quickly, and has a positive effect on stimulants.